At what point does the graph of 5x + 4y = 12 intersect the y-axis?a. (0, 3)
b. (0, -3)
c. (3, 0)
d. (5, 0)
e. (0, -5)

Answers

Answer 1
Answer: To find the y-intercept, we need to re-arrange the equation given to y=mx+c, where c is the y-intercept
To do this to 5x + 4y = 12, we need to have only y on the left side, so subtract 5x from each side, to get
4y = 12 - 5x, or
4y = -5x + 12
Now we need to isolate y, so divide each side by 4
y = 5/4x + 3
So the y-intercept will be at +3, and the y intercept is always on x = 0, so the co-ordinate will be (0, 3), which is a.

Related Questions

Graph h(x)=8 I x+1 I -1.
Sam gave jen 1/2 of his jujubes .jen ate 1/2 ofthe jujubes and gave rest to kyle.kyle kept 8 of the jujubes and gave the last 10 to kim .how many jujubes did Jen eat?
Help, please. I really need help one this
Use the stem-and-leaf plot below to find the mean, median, and mode of the data set. Round to the nearest wholenumberStem Leaf5 2, 2, 2.8. 1,5,99. 3,4,61. 2,7
The width of classroom is 4 meters less than the length, and the area is 192m^2. If the length is x m, find an equation in x and hence, find the dimensions of the classroom

Help Math Analysis !!!!

Answers

3x + 4y = 17     (1)
-4x - 3y = -18    (2)

multiply equation (1) by 4 and equation (2) by 3 to eliminate x

(× 4)  12x + 16y = 68     (1)
(× 3)  -12x - 9y  = -54     (2)
---------------------------------------------Add
7y = 14
  y = 2

Replace y = 2 into equation (1) 3x + 4y = 17 to find x

3x + 4(2)= 17 
3x + 8 = 17
3x = 9
  x = 3

Anwser:
(3,2)

Hope it helps

Nimisha wants to draw a wheel like the one shown. Each shaded part of the wheel should be one-third of each unshaded part. What should be the degree measure of the angle formed at the center by each shaded part?

Answers

Answer:

Each shade has a 22.5 degree angle from the middle

Each unshaded has a 67.5 degree angle from the middle.

Step-by-step explanation:

You can solve this by making each unshaded part equal to x and each shaded part equal 1/3x it is a circle so it has to equal 360 so you end up with:

x + 1/3x + x + 1/3x + x + 1/3x + x + 1/3x = 360

Combine Like terms:

16/3x = 360

Multiply both sides by the opposite:

(3/16) (16/3x) = (360) (3/16)

x=135/2 or x=67.5

Then you can plug 67.5 in for x:

1/3x ---> 1/3(67.5) = 22.5

Divide 36 by the difference of 16 and 4

Answers

The answer is 3. First you solve 16-4 and you get 12. Then you solve 36/12 which equals 3.
You subtract ➡️. first 16-4= 12
Then divide ➡️. 36 divided by 12 is =3 so the answer is 3

Given that (2,3) is on the graph of f(x),find the corresponding point for the function f(x) - 4

Answers

The corresponding point for the function f(x) - 4 is (2, -1)

What is a function?

A function in mathematics set up a relationship between the dependent variable and independent variable. on changing the value of the independent variable the value of the dependent variable also changes.

given that (2,3) is on the graph of f(x)

So, for x = 2, f(x) = f(2) = 3

Now, define another function g(x) such that

g(x)   =   f(x)  -  4

g(2)   =   f(2)  -  4

g(2)   =   3  -  4  =  -1

Hence, corresponding point for the function f(x) - 4 is (2, -1)

To know more about function follow

brainly.com/question/2833285

#SPJ2

given that (2,3) is on the graph of f(x)

So, for x = 2, f(x) = f(2) = 3

Now, define another function g(x) such that

g(x) = f(x) - 4

So g(2) = f(2) - 4 = 3 - 4 = -1

Hence, corresponding point for the function f(x) - 4 is (2, -1)

A man with mass 81 kg lies on the floor. What is the normal force on the man?A. 855 N
B. 794 N
C. 713 N
D. 820 N

Answers

F=m\cdot g\ \ \ \ \wedge\ \ \ \ g\approx9.8\ m/s^2\n \nF\approx81\ kg\cdot9.8\ m/s^2=793.8\ (kg\cdot m)/(s^2) \approx794\ N\ \ \ \Rightarrow\ \ \ Ans.\ B
Forces come in pairs, so the force of gravity (9.8 N) with the mans weight (794N) on the earth is counteracted with the normal force ( the force of the earth back on the man) which is the same

Rewrite in simplest terms (10x−2y)−(x+3y)

Answers

Answer:

The simplified expression is 9x - 5y.


To simplify the expression we can distribute the negative sign to the parenthesis. We can also get rid of the parenthesis of both terms once we have distributed.

(10x-2y)-x-3y

10x-2y-x-3y

We can now combine like terms:

9x-5y

So, our simplified expression is 9x - 5y.